DETEKSI SUPLEMEN BEBAS KANDUNGAN DNA BABI YANG TERSEDIA DI RUMAH SAKIT KRAKATAU MEDIKA CILEGON DENGAN METODE REAL TIME PCR - Firman Rezaldi; Alfi Hardian; Hadi Susilo; Sumarlin US (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2022)
Indonesia is a country where the majority of the population is seasonal, so the halalness of a product is very important. Supplements are one of the products that are widely circulated in Indonesia, so they must provide halal guarantees for these products as evidenced by the existence of a halal label. In its circulation, supplements are still found without a halal label, so an authentication is needed to prove the halalness of the product. This study was conducted to prove the halalness of supplement products without halal labels by taking five samples randomly from the Pharmacy Installation of Krakatau Medika Hospital which were analyzed by the Real Time PCR method. The DNA of the five supplement samples was isolated using a Commercial Kit and the isolated DNA was amplified by Real Time PCR for 30 cycles. From the results of the Real Time PCR analysis, it was found that no pork DNA contaminants were found in the five supplement samples analyzed Keywords: Supplement, Realtime PCR, Pig DNA, Halal